An empirical study to evaluate factors affecting customer satisfaction on the adoption of Mobile Banking Track: Financial Management (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Researcher needs to drive the effect of factors like ease of use, mobile atmosphere, perceived responsive, image of bank, perceived security, perceived risk, performance benefits, social influence, and hedonic motivation towards mobile banking. Here researcher measure direct and indirect effects of factors influences. In this research, luenlufeuu trust and performance expectancy are consider as mediating variableu whereas innovative is crfuiseo as ctaerroitu moderating variable. The data was gathered from 251 users of mobile banking through structure questionnaire with seven point scale. Descriptive Analysis Research Methodology was performed to test the research hypotheses where as multiple regression and path analysis performed with Advance. research sepeurpes an efficient model to evaluate intra-relationships amongst the factors affecting customer satisfaction on adopting of mobile banking. The results of research confirmed significant direct effects of factors like ease of use, mobile atmosphere, perceived responsive, image of bank, perceived security, perceived risk, performance benefits, social influence, and hedonic motivation towards mobile banking. Research also ensures the significant mediating effect of  ,luenlufeuutrust and performance expectancy as well as ctaerroitu moderating effect of innovative. This is unique effort of researcher for developing structural model for mobile .gtfkifr This study will help in understanding the concept of interrelation between different factors directly and indirectly correlated to mobile banking. These results provide insights for banks and mobile application providers to develop strategies that will enhance perceived value, customer experience and customer satisfaction. The main limitation of this paper is that sample population has been restricted to the users of mobile banking in major cities of Gujarat region only.